Description of a New Species of Aquilonastra (Asteroidea: Valvatida: Asterinidae) from Langkawi Island, Malaysia - Itaru Kobayashi; Masaki Yamamoto; Mikihito Arai; Sau Pinn Woo; Toshihiko Fujita (Species Diversity)
A new species of Aquilonastra O’Loughlin in O’Loughlin and Waters, 2004 is described on the coast of Langkawi Island, Malaysia. This new species is distinguished from 32 congeners based on the number of arms, madreporites, superomarginal and subambulacral spines, the absence of secondary abactinal plates, the shape of abactinal spines, and the attachment site of gonads.